Rhododendron boninense Nakai 1920 - Watanabe-Toma, Kana; Ohi-Toma, Tetsuo; Murata, Jin (Zenodo, 2011)
Rhododendron boninense Nakai (1920: 324) Lectotype (designated here)— JAPAN: Bonin Chichijima Tsutsuji-yama: 8 July 1920, T. Nakai s.n. (TI [43237a]!; isolectotype: TI [43237b]!). Distribution: Japan (Chichijima in the Bonin Islands). Rhododendron boninense was described as a new taxon in Japanese, without citation of specimens (Nakai 1920). In the description of morphological characters of the species, Nakai mentioned that he examined withered flowers with stamens and a pistil because the flowering season was over. The following year, the species was redescribed in Latin based upon specimens collected from Tsutsuji-yama on Chichijima by T. Nakai and H. Toyoshima (Nakai 1921). Toyoda (1981) and Yamazaki (1996) considered that the Nakai’s (1921) description of the species was valid and recognized the specimen with flowers ( H. Toyoshima s.n. , 1921, TI) as the holotype of the species. However, ICBN Art 36.1. states that after 1 January 1935 the name of a new taxon must be accompanied by a Latin description or diagnosis or by a reference to a previously and effectively published Latin description or diagnosis (McNeill et al. 2006). Conversely, names with a description or diagnosis written in Japanese are valid before 1935. Therefore, the valid publication of this taxon is not Nakai (1921) but Nakai (1920). In this case, no claim can be made that the specimen collected by H. Toyoshima in 1921 is the holotype. The specimen ( T. Nakai s.n., 8 July 1920, TI) collected in Tsutsujiyama on Chichijima, which consists of two branches with withered flowers, is consistent with the original description in Japanese (Nakai 1920). Therefore, we choose the larger of the two branches as the lectotype. : Published as part of Watanabe-Toma, Kana, Ohi-Toma, Tetsuo & Murata, Jin, 2011, Typification of Angiospermae described from the Bonin Islands 1: Metachlamydeae, pp. 51-58 in Phytotaxa 33 on pages 52-53, DOI: 10.11646/phytotaxa.33.1.4, http://zenodo.org/record/4894593 : {"references": ["Nakai, T. (1920) Ogasawara-no-tsutsuji. Botanical Magazine (Tokyo) 34: 324.", "Nakai, T. (1921) Notulae ad plantas Japoniae et Koreae XXV. Botanical Magazine (Tokyo) 35: 139 - 153.", "Toyoda, T. (1981) Flora of Bonin Islands. Aboc Co. Ltd., Tokyo.", "Yamazaki, T. (1996) A revision of the genus Rhododendron in Japan, Taiwan, Korea and Sakhalin. Tsumura Laboratory, Tokyo.", "McNeill, J., Barrie, F. R., Burdet, H. M., Demoulin, V., Hawksworth, D. L., Marhold, K., Nicolson, D. H., Prado, J., Silva, P. C., Skog, J. E., Wiersema, J. H. & Turland, N. J. (Eds) (2006) International Code of Botanical Nomenclature (Vienna Code) adopted by the Seventeenth International Botanical Congress Vienna, Austria, July 2005. A. R. G. Gantner Verlag, Ruggell. [Regnum Veg. 146]"]}